2021
DOI: 10.1038/s41467-021-24125-5
|View full text |Cite
|
Sign up to set email alerts
|

Tailored cobalt-salen complexes enable electrocatalytic intramolecular allylic C–H functionalizations

Abstract: Oxidative allylic C–H functionalization is a powerful tool to streamline organic synthesis as it minimizes the need for functional group activation and generates alkenyl-substituted products amenable to further chemical modifications. The intramolecular variants can be used to construct functionalized ring structures but remain limited in scope and by their frequent requirement for noble metal catalysts and stoichiometric chemical oxidants. Here we report an oxidant-free, electrocatalytic approach to achieve i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(38 citation statements)
references
References 56 publications
0
36
0
1
Order By: Relevance
“…Alkenes are versatile building blocks in modern organic synthesis [34] . It has been reported that alkenes could be attacked by electrogenerated thiophenol radicals, [35] alcohol radicals, [9d,36] and nitrogen radicals [9a,37] . In this chapter, we demonstrate the reactions involving sulfonyl compounds as radical precursors and alkenes as radical acceptors.…”
Section: Reaction Of Alkenesmentioning
confidence: 78%
“…Alkenes are versatile building blocks in modern organic synthesis [34] . It has been reported that alkenes could be attacked by electrogenerated thiophenol radicals, [35] alcohol radicals, [9d,36] and nitrogen radicals [9a,37] . In this chapter, we demonstrate the reactions involving sulfonyl compounds as radical precursors and alkenes as radical acceptors.…”
Section: Reaction Of Alkenesmentioning
confidence: 78%
“…Building on our previous studies on intramolecular allylic C−H functionalizations, [39] we surmise that the acidic carbon nucleophile can be oxidized electrocatalytically with a cobalt‐based molecular catalyst to generate an electron‐deficient carbon‐centered radical, [39–41] which then adds to the alkene to afford an alkyl radical. The newly formed radical center significantly weakens the γ‐C−H bond [bond dissociation energy (BDE) <36 kcal mol −1 ], [42] enabling effective hydrogen atom transfer (HAT) to the cobalt catalyst to furnish the alkene alkylation product [39, 43] . In contrast to the organometallic C−H activation, the presence of substituents at the β‐ or γ‐positions of the alkene substrate should not interfere with the radical reactions; in fact, they might even be beneficial, thus expanding the substrate scope to branched alkenes.…”
Section: Methodsmentioning
confidence: 99%
“…While the voltammogram exhibited no change with the addition of 2 and Na 2 CO 3 , the reduction wave for [Co III ]/[Co II ] disappeared in the presence of 2 and NaOMe but without the observation of a catalytic current [50] . These results suggested that the electrochemically produced [Co III ] species reacted with the conjugate base of 2 through inner‐sphere electron transfer [39] . Na 2 CO 3 was barely soluble in the mixed solvent of DMF/MeCN (1 : 1), explaining its failure in promoting the reaction of [Co III ] with 2 under the static conditions employed for the CV testing.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was seen that the redox catalyst played a vital role in the electrochemical transformation (Scheme 70). [129] A series of starting materials were employed for the reaction and gram scale synthesis of the desired product was achieved. The reaction proceeded via anodic oxidation of tris(2,4‐dibromophenyl)amine to generate the radical cation which catalyzes the oxidation of olefin through SET to form the radical cation.…”
Section: Intermolecular and Intramolecular Cyclizationmentioning
confidence: 99%